Whole-exome sequencing uncovers the genetic basis of hereditary concomitant exotropia in ten Chinese pedigrees - Wenhua Duan; Taicheng Zhou; Xiaoru Huang; Dongqiong He; Min Hu (BMC Medical Genomics)
Abstract Purpose To explore possible pathogenic genes for concomitant exotropia using whole-exome sequencing. Methods In this study, 47 individuals from 10 concomitant exotropia (including intermittent exotropia and constant exotropia) pedigrees were enrolled. Whole-exome sequencing was used to screen mutational profiles in 25 affected individuals and 10 unaffected individuals. Sanger sequencing and in silico analysis were performed for all participants. Two target genes were used to capture the sequences of 220 sporadic samples. Results All 10 concomitant exotropia pedigrees presented autosomal dominant inheritance with childhood onset (3.35 ± 1.51 years old). Eleven different missense variants were identified among seven potential pathogenic genes (COL4A2, SYNE1, LOXHD1, AUTS2, GTDC2, HERC2 and CDH3) that cosegregated with pedigree members. All variants were predicted to be deleterious and had low frequencies in the general population. Distinct variants of COL4A2 were present in three pedigrees, and distinct variants of SYNE1 were present in two pedigrees. Fifteen variants in AUTS2 and four variants in GTDC2 were identified in 220 patients with sporadic concomitant exotropia using a target-capture sequencing approach. Conclusion This is the first study to explore the genetic mechanism of concomitant exotropia and identify seven associated genes (COL4A2, SYNE1, LOXHD1, AUTS2, GTDC2, HERC2 and CDH3) that may be candidate genes causing concomitant exotropia. More samples and in-depth studies are needed to verify these findings.